Urine Microbial Spectrum In Children With Urinary Tract Infection - Belykh Natalia Anatolievna; Tereshchenko Sofia Viktorovna; Anikeeva Natalia Alexandrovna; Mukhamadieva Lola Atamuradovna; Kuldashev Sardor Furkatevich (Global Scientific Publishing, 2023)
The aim of the study was to study the spectrum of urinary pathogens and their sensitivity to antimicrobial drugs (AMP) in urinary tract infections (UTIs) in children of the Ryazan region. We carried out a retrospective local laboratory monitoring of the urine microflora and analyzed its sensitivity to antibiotics in 111 patients aged 2 months to 17 years who received conventional therapy. The study group consisted of 75 (67.6%) girls and 36 (32.4%) boys. To test the sensitivity of pathogens to antimicrobials, a phenotypic diffusion test and an analytical test for carbapenem inactivation were used. It was established that the predominant causative agents of urinary incontinence were Escherichia coli (50.4%) and K. pneumonia (14.4%). Resistance determinants were found in 9.0% and 2.7% of E. coli and urological strains of K. pneumonia, respectively. The main mechanism of resistance was the production of broad-spectrum plasmid β-lactamases. III-IV generation cephalosporins, aminoglycosides, fosfomycin (100%), nitrofurantoin (91.3%) and aminopenicillins (76.1-86.9%) showed the highest activity against E. coli. With regard to K. pneumonia, the most effective (100%) were III-IV generation cephalosporins and aminoglycosides. All resistant pathogens were sensitive to cefoperazone, sulbactam, meropenem, imipenem, aminoglycosides (100%); nitrofurantoin and fosfomycin were most active against E. coli. In children with UTI in the Ryazan region, gram-negative bacteria (85.6%) prevailed in the urine, enterobacteria predominated (81.1%). Antimicrobial resistance determinants were quite rare (17.8%) in these urine isolates; they were all class A ESBL producers
Keywords: antibiotic therapy; antibiotic resistance; children; urinary tract infections